Direitos das mulheres e das pessoas que gestam à interrupção voluntária da gestação: um estudo teórico reflexivo - Mariana Bernardo de Brito (2024)
This is a reflective theoretical work on the current scenario of the right to voluntary termination of pregnancy in Brazil and its cultural and political implications. To carry out the study, feminist theories and reproductive rights were used as theoretical references. Objective: The study proposes to analyze the interruption of pregnancy from the perspective of feminism, intersectionality, and the right of female bodies regarding the decision to interrupt a pregnancy or not, debate the voluntary interruption of pregnancy in Brazil as a reproductive right, and discuss the reproductive rights in Brazil and in South American countries that have decriminalized abortion. The methodology adopted was a narrative review, in which official documents relevant to Brazilian legislation and studies on the topic over the last ten years were consulted. The time frame is due to the resurgence in relation to the topic, clearly with a conservative bias, and a regulator of female bodies after the coup d'état in 2016, in which the first female president of Brazil was deposed. Furthermore, research was conducted with news from information vehicles circulating in the country which addressed the termination of pregnancy as a reproductive right at risk and legislation from other countries, especially in South America. This shows that termination of pregnancy in Brazil should be seen not only as a right of women and people who are pregnant, but also as a public health issue, as shown by research in the area. Supported by law in certain cases, it does not reach all women or people who are pregnant who need it in contexts different from what the law provides. In recent years, access to this right has been hampered by political-ideological issues associated with the domination and historical disciplinaryization of bodies, female and different from ones imposed by patriarchal society. Furthermore, in Brazil, the advance of conservatism and criticism of the voluntary termination of pregnancy has been noticeable, including in the cases provided for by law. In 2023, since the beginning of the trial by the Federal Supreme Court of ADPF 442, with the vote of the rapporteur, Minister Rosa Weber, the debate is in vogue in the country and it is necessary to discuss the topic clearly and objectively based on scientific evidence and, following the example of other countries with progressive legislation such as Argentina, Colombia, Guyana, French Guiana and Uruguay, so that termination of pregnancy can be understood as a reproductive right of women and people who are pregnant.